University Commitment, Socioeconomic Background, and Brand Trust in Shaping Loyalty in Medan - Ratih Amelia; Tyus Windi Ayuni (CV. AFDIFAL MAJU BERKAH, 2026)
This research investigates the key drivers of student loyalty within private higher education institutions in Medan, emphasizing institutional commitment, socioeconomic status, and brand trust. A quantitative design was applied through Partial Least Squares–Structural Equation Modeling (PLS-SEM), utilizing data from 450 active students proportionally drawn from universities, institutes, colleges, and polytechnics in the region. The study employed a structured questionnaire developed from validated indicators and assessed using a five-point Likert scale. The findings reveal that all three constructs exert a significant and positive influence on student loyalty. Among them, brand trust emerged as the most influential factor, with a path coefficient of 0.426, t-value of 7.582, and p-value of 0.000. Institutional commitment followed, with a path coefficient of 0.287, t-value of 4.926, and p-value of 0.000, while socioeconomic background also demonstrated a notable effect (path coefficient 0.218, t-value 3.714, p-value 0.000). The R² value of 0.624 indicates that these variables collectively explain 62.4% of the variance in student loyalty, leaving 37.6% attributable to other factors beyond the model. Overall, the study underscores that student loyalty is shaped not only by academic services but also by institutional credibility, reliability in fulfilling commitments, and sensitivity to students’ socioeconomic realities. From a theoretical standpoint, the research enriches existing scholarship by integrating institutional, socioeconomic, and trust-based dimensions into a unified loyalty framework. Practically, the results suggest that private higher education institutions in Medan should prioritize strengthening brand trust, sustaining institutional commitment, and designing inclusive services to foster student loyalty and enhance competitiveness